Active and Creative Islamic Religious Education Learning Methods at SMP Muhammadiyah 57 Medan - Badri Girsang, Hamidah Nurul; Siti Muti’ah; Ayustia, Husni; Yusmeini, Dinda; Ulya, Nadiatul (Journal of General Education Science, 2023)
The problem in this study will reveal the application of active and creative learning methods at Madrasah Aliyah Darul Ulum Banyuanyar Palengaan Pamekasan, this research aims to be able to describe the learning methods applied at SMP MUHAMMADIYAH 57 MEDAN. The type of data from observations is in the form of in-depth field notes and documentation in the form of archived notes. The research data source is the primary data source in the form of interviews and field observations with informants, while the secondary data source is in the form of document study results obtained in the research. The data collection procedure uses three data collection techniques, namely: participant observation techniques, in-depth interviews, and study of documents and using a qualitative descriptive method with primary data collection through interviews and observation while secondary data obtained through documentation. The research results show that the application of learning methods in Madrasahs is not yet effective because they still use conventional methods such as the lecture method, the discussion method, and the demonstration method. It is necessary to develop a variety of learning methods so that the learning process becomes active and creative.